Impact of Photovoltaic Microgrid System on Renewable Energy Building - Attia, Hussain (International Journal of Energy Economics and Policy, 2021)
This paper analyzes the supportive function of the photovoltaic PV system in integrating the microgrid role to deliver the necessarily clean electricity to the individual dwellings. The study focuses on the merit of the flexibility in designing a renewable energy PV system in terms of power quality and quantity, in addition to reducing the air pollution by reducing the dependency on the conventional power generation station. A comparison between a direct current DC microgrid and an alternating current AC microgrid is shown in terms of system's components and requirements. The process of an algorithm for the Maximum Power Point Tracking MPPT to guarantee a higher level of harvested energy is also shown. A PV system design is introduced in this study for a desired power level generating to satisfy the electricity requirements of a small scale dwelling with a maximum power delivering capability of 9 kW. MATLAB/Simulink is adopted to investigate and evaluate the PV system performance in guaranteeing the MPPT functioning. Keywords: Renewable energy sources, Microgrid system, traditional power station, Photovoltaic PV panel, MPPT algorithm, MATLAB/Simulink. JEL Classifications: C3689, D4, Q24 DOI: https://doi.org/10.32479/ijeep.11603